A kind of high-fluidity micro-expansion ultra-high performance concrete and its preparation method
By adopting large-scale micro-expansion ultra-high performance concrete formula and internal maintenance-micro-activated agglometer system, the existing ultra-high-performance concrete has problems such as large contraction and difficulty in improving mechanical performance during the preparation process. Performance, work performance and volume stability, and reduced preparation costs.
Patent Information
- Application Number
- CN202310772339.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-28
AI Technical Summary
During the preparation process, existing ultra-high performance concrete has problems such as large shrinkage, difficulty in improving mechanical properties, increased construction difficulty and high preparation cost.
The formula of large-current micro-expansion ultra-high performance concrete, including cement, silico ash, molten coal ash microdes, heavy calcium carbonate, expansion, micro-active-high-strength micropore composite aggregate, water, polycarboxylic acid reducing water reduction reduction The agent and steel fiber, through the internal maintenance-micro-activated osteogenic system and the roller-occlusion state improvement technology, combined with multi-grade feed technology and large water glue ratio, adjust the adhesive and liquidity of the slurry.
Realize the good mechanical performance, work performance and volume stability of ultra -high performance concrete. The 28D pressure resistance can reach 250MPA or more, the anti -folding strength can reach more than 50 MPa, and has a long -term micro -expansion effect, which significantly reduces the preparation process. Complexity and cost.
Smart Images

Figure BDA0004308287280000091 
Figure HDA0004308287290000011 
Figure HDA0004308287290000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a high-fluidity micro-expansion ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) refers to a fiber-reinforced cement-based composite material with ultra-high mechanical properties, durability and toughness. It is usually designed based on the closest packing theory, using sub-micron particles (silica fume) to fill the stacking gaps between micron particles (cement, fly ash, mineral powder), and using micron particles (cement, fly ash, mineral powder) to fill the stacking gaps between millimeter particles (aggregates), to obtain concrete with a compressive strength of more than 120MPa. However, the amount of adhesive used in ultra-high performance concrete is much higher than that of ordinary concrete, and in order to reduce the interface transition zone and improve toughness, it is usually necessary to remove coarse aggregates, which makes UHPC shrink larger and has a higher risk of cracking.
[0003] With the deepening of research at home and abroad, its mechanical properties and volume stability are also constantly improving. For example, the Chinese invention patent with publication number CN113480272A discloses a self-curing micro-expansion ultra-high performance concrete and its preparation method, which makes the obtained ultra-high performance concrete have micro-expansion effect through the interaction between the internal curing material ceramsite and the expansion agent, but the mechanical properties are still not improved. The Chinese invention patent with publication number CN113024189A discloses a high-toughness and high-adhesion C250 ultra-high-strength hybrid fiber concrete and a preparation method thereof. The high-toughness and high-adhesion C250 ultra-high-strength hybrid fiber concrete is prepared by adding three different-sized fibers of ramie fiber, basalt fiber, and CaCO3 whisker and active mineral admixtures of different particle size ranges such as fly ash, straw ash, silica ash, and nano-silicon, and a carboxyl-modified polyvinyl alcohol polymer that can fill the pores and connect the three fibers, a nano-silicon / graphene oxide dispersion that acts as a template, and chemical admixtures such as a water reducer and an activator. Although this method can produce ultra-high performance fiber concrete with a compressive strength of more than 250MPa, due to the high viscosity of UHPC itself, it is extremely difficult to disperse nano-scale materials such as nano-silicon / graphene oxide, modified carbon nanotubes, graphene oxide, and ultra-fine fibers such as ramie fiber, basalt fiber, CaCO3 whisker, and cellulose fiber in UHPC. Although it is pre-dispersed using a special dispersion process and used to prepare UHPC, the resulting UHPC still has the problem of poor working performance. Among them, the slump of the obtained UHPC is only 90-105mm. When it is used in actual engineering, the construction difficulty increases, and the cost of the above-mentioned raw materials is high. The entire UHPC preparation process is extremely complicated, which greatly increases the preparation cost of UHPC, thereby greatly increasing the difficulty of promoting and applying UHPC.
[0004] Therefore, it is of great research and application significance to further explore ultra-high performance concrete with micro-expansion effect while taking into account good working performance and mechanical properties, and effectively simplify its preparation process and reduce preparation costs. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-flow micro-expansion ultra-high performance concrete with good mechanical properties, workability and volume stability, in order to solve the problems and shortcomings of existing ultra-high performance concrete, such as large shrinkage and difficulty in significantly improving mechanical properties.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A high-fluidity micro-expansion ultra-high performance concrete comprises the following components by weight: 700-800 parts of cement, 120-150 parts of silica fume, 90-110 parts of fly ash micro-beads, 80-100 parts of heavy calcium carbonate, 40-60 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 220-240 parts of water, 10.5-12.5 parts of polycarboxylate water-reducing agent, and steel fiber accounting for 2.5-3.0% of the volume of the low-shrinkage ultra-high performance concrete; the micro-active-high-strength microporous composite aggregate is mixed with cement clinker and high-alumina bauxite aggregate in a mass ratio of (1-3):(7-9).
[0008] Preferably, the micro-active-high-strength microporous composite aggregate is prepared by mixing cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:(7-9).
[0009] The present invention composites cement clinker and high-alumina bauxite aggregate to form an aggregate system of UHPC, forming an internal curing-micro-activated aggregate system, wherein the microporous structure of the high-alumina bauxite aggregate enables it to absorb a portion of water during the slurry stirring process. On the one hand, this portion of water can be slowly released during the slurry hydration and hardening process to adjust the internal humidity of the UHPC, play an internal curing role, and reduce the shrinkage of the UHPC. On the other hand, the released water can also promote the hydration of the micro-active cement clinker, generate hydration products such as CSH gel to strengthen the connection between aggregate particles, thereby effectively enhancing the interface transition zone of the entire aggregate system, and then effectively improving the mechanical properties of the entire system; at the same time, it can effectively improve the working performance and durability of the UHPC system. In addition, the expansion agent in the present invention reacts with water in the system, and under the internal curing action of the high-alumina bauxite aggregate, it continuously produces expansion substances to compensate for the shrinkage of UHPC at each age, so that the UHPC has a long-term micro-expansion effect. At the same time, the present invention forms a ball-bite system by increasing the water-binder ratio of the system and compounding microspheres with ball shape and heavy calcium with angular structure, thereby adjusting the cohesiveness and fluidity of the entire system, and effectively solving the problem that when high-alumina bauxite is used for UHPC preparation, the UHPC slurry loses state quickly and has poor fluidity due to the microporous structure of the high-alumina bauxite, and the adsorption of the expansion agent on the water reducer leads to a reduction in the dispersing effect of the water reducer on the system, thereby adversely affecting the working performance and mechanical properties of the entire system.
[0010] Optionally, the expansion agent is mainly composed of a mixture of a calcium oxide expansion agent and gypsum in a mass ratio of (2-3):1.
[0011] The calcium oxide expansion agent in the expansion agent of the present invention is hydrated to generate calcium hydroxide Ca(OH)2. While the solid phase volume increases, the local accumulation of hydration products increases the pore volume and causes the slurry volume to expand. Gypsum participates in cement hydration to generate calcium aluminate. On the one hand, it can compensate for the shrinkage of UHPC together with the calcium oxide expansion agent, so that UHPC has a micro-expansion effect. On the other hand, it can stimulate the activity of fly ash microbeads, optimize the composition of hydration products, and improve the problem of decreased density of slurry structure caused by the calcium oxide expansion agent, thereby effectively improving the mechanical properties of the entire system.
[0012] Optionally, the cement is ordinary Portland cement or Portland cement with a grade not less than 42.5.
[0013] Optionally, the water demand ratio of the silica fume is not greater than 125%, and the 28d activity index is not less than 105%.
[0014] Optionally, the fly ash microspheres have a water demand ratio of ≤95% and a 28d compressive activity index of ≥110%.
[0015] Optionally, the fineness of the heavy calcium carbonate is not less than 325 mesh and not more than 600 mesh.
[0016] In order to ensure that the added heavy calcium carbonate has both a good performance improvement effect on the entire system and a good micro-aggregate filling effect, the fineness of the heavy calcium carbonate is reasonably selected so that the obtained UHPC has good mechanical properties and working performance.
[0017] Optionally, the gypsum is anhydrite with a particle size of 260-325 meshes.
[0018] Optionally, the steel fiber has a diameter of 0.14-0.16 mm, a length of 9-11 mm, and an aspect ratio of 60-70.
[0019] In order to ensure that the entire UHPC system has a good strong skeleton system and good internal curing effect, the present invention adds high-alumina bauxite aggregate and cement clinker particles with larger particle sizes, resulting in limited distribution space of steel fibers inside the formulated UHPC, which makes it easy for them to be unevenly distributed in the entire slurry system, or even clustered, thereby adversely affecting the mechanical properties and working performance of UHPC. To this end, the present invention reasonably selects the size of steel fibers based on the spatial size distribution of the entire system, so that an effective three-dimensional mesh overlap structure is formed between the steel fibers and the aggregates, so that the obtained UHPC has good mechanical properties, working performance and volume stability performance.
[0020] Optionally, the water reduction rate of the polycarboxylate water-reducing agent is ≥25%.
[0021] Optionally, the cement clinker is mainly composed of particles with the following particle sizes, measured by mass percentage: 0.15-0.3 mm 5-10%, 0.3-0.6 mm 10-20%, 0.6-1.18 mm 40-50%, and 1.18-2.36 mm 20-30%.
[0022] Preferably, the cement clinker is Portland cement clinker.
[0023] In order to ensure that the entire cement clinker system has high activity without reducing the working performance of the entire system, and at the same time ensure the strong skeleton effect of the entire aggregate system, the particle size of the cement clinker is reasonably designed, which effectively improves the strengthening effect of the cement clinker on the high-aluminum aggregate interface transition zone, thereby greatly improving the mechanical properties of UHPC without adversely affecting the working performance.
[0024] Optionally, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes, in percentage by mass: 0-1 mm 50-60%, 1-3 mm 40-50%.
[0025] Preferably, the alumina content of the high alumina aggregate is not less than 80 wt%.
[0026] In order to ensure that the entire aggregate system has both good internal curing effect and good skeleton effect, and at the same time make the aggregate system and the powder system have good working performance matching, the particle size of the high-alumina bauxite aggregate is reasonably designed, so that the obtained UHPC has good working performance, mechanical properties and volume stability.
[0027] The above-mentioned method for preparing a kind of high-fluidity micro-expansion ultra-high performance concrete:
[0028] 1) Mix and stir the weighed water and silica fume to obtain slurry A;
[0029] 2) adding weighed cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to the obtained slurry A, and continuing stirring to obtain slurry B;
[0030] 3) adding the weighed micro-active-high-strength microporous composite aggregate to the obtained slurry B, and continuing to stir to obtain slurry C;
[0031] 4) Add the steel fiber to the obtained slurry C and stir evenly to obtain high-fluidity micro-expansion ultra-high performance concrete.
[0032] In the above scheme, the stirring time in step 1) is 20-40s.
[0033] In the above scheme, the stirring time in step 2) is 1.0-1.5 min.
[0034] In the above scheme, the stirring time in step 3) is 1.5-2.0 min.
[0035] In the above scheme, the stirring time in step 4) is 1.0-1.5 min.
[0036] The present invention first fully disperses the silica fume in water, effectively avoiding the problem that the silica fume has a large specific surface area and strong adsorption. When the silica fume is directly mixed with other raw materials and then stirred with water, there is electrostatic adsorption between the other raw materials, resulting in a long time for the slurry to come out of the state, especially for the high-alumina bauxite aggregate with a microporous structure used in the present invention. In addition, the present invention first disperses the silica fume in water, which can reduce its adsorption to the water reducer, thereby effectively improving the dispersion efficiency of the water reducer to other powder particles, and then effectively improving the hydration degree of the entire system. At the same time, the present invention adopts a multi-stage feeding, mixing and stirring method, which can further improve the dispersion efficiency of the entire system, thereby facilitating the improvement of the mechanical properties of the system.
[0037] The high-flow micro-expansion ultra-high performance concrete prepared according to the above scheme has a 28-day compressive strength of more than 250MPa, a flexural strength of more than 50MPa, an initial expansion of 720-770mm, a 1h expansion of 680-725mm, an expansion of 231με under 7d autogenous shrinkage test, and an expansion of 113με under 180d shrinkage test. The chloride ion diffusion coefficient at 28d can be as low as 3.9×10 -14 m 2 ·s -1 the following.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention combines internal curing-micro-activation enhancement technology, ball-bite state improvement technology, expansion agent expansion excitation effect, and space size balance technology, and cooperates with a multi-stage feeding process and a large water-binder ratio (≥0.20), so that the slurry has a good working state while ensuring that each raw material can be effectively dispersed and fully reacted to form a dense hardened slurry structure, and at the same time, a good fiber lap effect and a long-term micro-expansion effect are formed, thereby successfully formulating a large-flow micro-expansion ultra-high performance concrete with good working performance, mechanical properties and volume stability performance;
[0040] 2. Compared with the existing UHPC performance improvement methods, the preparation process involved in the present invention is simple and has low preparation cost, which is conducive to popularization and application; and the entire preparation process can be controlled within 5 minutes, which significantly reduces the energy consumption of slurry preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The autogenous shrinkage test results of the ultra-high performance concrete obtained in Example 1 and Comparative Example 5 are shown;
[0042] Figure 2 The drying shrinkage test results of the ultra-high performance concrete obtained in Example 1 and Comparative Example 5 are shown. DETAILED DESCRIPTION
[0043] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0044] In the following examples, the cement used is P·O52.5 grade ordinary Portland cement;
[0045] The water requirement ratio of silica fume is 115%, and the 28d activity index is 118%;
[0046] The water demand ratio of fly ash microspheres is 91%, and the 28d compressive activity index is 112%;
[0047] The fineness of heavy calcium carbonate is 325 mesh;
[0048] The average diameter of the steel fibers is 0.15 mm, the average length is 10 mm, and the average aspect ratio is 67;
[0049] Polycarboxylate water reducer is a powdered polycarboxylate water reducer with a water reduction rate of 25%;
[0050] The gypsum is anhydrite, and its particle size is 325 mesh;
[0051] The 7-day limited expansion rate of calcium oxide expansion agent in water is 0.042%. The alumina content of high-alumina bauxite aggregate is 80.05%;
[0052] Cement clinker is silicate cement clinker.
[0053] Example 1
[0054] A high-flow micro-expansion ultra-high performance concrete, comprising the following components by weight: 700 parts of cement, 120 parts of silica fume, 90 parts of fly ash micro-beads, 80 parts of heavy calcium carbonate, 50 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 220 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the high-flow micro-expansion ultra-high performance concrete;
[0055] The expansion agent is a mixture of calcium oxide expansion agent and gypsum in a mass ratio of 2:1; the micro-active-high-strength microporous composite aggregate is a mixture of cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:8; in terms of mass percentage, the cement clinker is mainly composed of particles with the following particle sizes: 0.15-0.3mm 5%, 0.3-0.6mm 20%, 0.6-1.18mm 50%, 1.18-2.36mm 25%; in terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm 50%, 1-3mm 50%;
[0056] The above-mentioned high-fluidity micro-expansion ultra-high performance concrete is prepared by the following method:
[0057] According to the above raw material ratio, water and silica fume were mixed and stirred for 30 seconds to obtain slurry A;
[0058] Add cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to slurry A and continue stirring for 1 min to obtain slurry B;
[0059] Add the micro-active-high-strength microporous composite aggregate into slurry B and continue stirring for 2 minutes to obtain slurry C;
[0060] Steel fiber was added to slurry C and stirred for 1 min to make the slurry evenly mixed to obtain high-fluidity micro-expansion ultra-high performance concrete.
[0061] Example 2
[0062] A high-flow micro-expansion ultra-high performance concrete, comprising the following components by weight: 750 parts of cement, 140 parts of silica fume, 110 parts of fly ash micro-beads, 100 parts of heavy calcium carbonate, 40 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 240 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the high-flow micro-expansion ultra-high performance concrete;
[0063] Among them, the expansion agent is a mixture of calcium oxide expansion agent and gypsum in a mass ratio of 2:1; the micro-active-high-strength microporous composite aggregate is a mixture of cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:8; in terms of mass percentage, the cement clinker is mainly composed of particles with the following particle sizes: 0.15-0.3mm 5%, 0.3-0.6mm 20%, 0.6-1.18mm 50%, 1.18-2.36mm25%; in terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm50%, 1-3mm50%.
[0064] The above-mentioned high-fluidity micro-expansion ultra-high performance concrete is prepared by the following method:
[0065] According to the above raw material ratio, water and silica fume were mixed and stirred for 30 seconds to obtain slurry A;
[0066] Add cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to slurry A and continue stirring for 1 min to obtain slurry B;
[0067] Add the micro-active-high-strength microporous composite aggregate into slurry B and continue stirring for 2 minutes to obtain slurry C;
[0068] Steel fiber was added to slurry C and stirred for 1 min to make the slurry evenly mixed to obtain high-fluidity micro-expansion ultra-high performance concrete.
[0069] Example 3
[0070] A high-flow micro-expansion ultra-high performance concrete, comprising the following components by weight: 800 parts of cement, 150 parts of silica fume, 110 parts of fly ash micro-beads, 100 parts of heavy calcium carbonate, 60 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 240 parts of water, 12.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the high-flow micro-expansion ultra-high performance concrete;
[0071] Among them, the expansion agent is a mixture of calcium oxide expansion agent and gypsum in a mass ratio of 2:1; the micro-active-high-strength microporous composite aggregate is a mixture of cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:8; in terms of mass percentage, the cement clinker is mainly composed of particles with the following particle sizes: 0.15-0.3mm 5%, 0.3-0.6mm 20%, 0.6-1.18mm 50%, 1.18-2.36mm25%; in terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm50%, 1-3mm50%.
[0072] The above-mentioned high-fluidity micro-expansion ultra-high performance concrete is prepared by the following method:
[0073] According to the above raw material ratio, water and silica fume were mixed and stirred for 30 seconds to obtain slurry A;
[0074] Add cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to slurry A and continue stirring for 1 min to obtain slurry B;
[0075] Add the micro-active-high-strength microporous composite aggregate into slurry B and continue stirring for 2 minutes to obtain slurry C;
[0076] Steel fiber was added to slurry C and stirred for 1 min to make the slurry evenly mixed to obtain high-fluidity micro-expansion ultra-high performance concrete.
[0077] Example 4
[0078] A high-flow micro-expansion ultra-high performance concrete, comprising the following components by weight: 750 parts of cement, 130 parts of silica fume, 100 parts of fly ash micro-beads, 90 parts of heavy calcium carbonate, 40 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 230 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the high-flow micro-expansion ultra-high performance concrete;
[0079] Among them, the expansion agent is a mixture of calcium oxide expansion agent and gypsum in a mass ratio of 3:1; the micro-active-high-strength microporous composite aggregate is a mixture of cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:8; in terms of mass percentage, the cement clinker is mainly composed of particles with the following particle sizes: 0.15-0.3mm 5%, 0.3-0.6mm 20%, 0.6-1.18mm 50%, 1.18-2.36mm25%; in terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm50%, 1-3mm50%.
[0080] The above-mentioned high-fluidity micro-expansion ultra-high performance concrete is prepared by the following method:
[0081] According to the above raw material ratio, water and silica fume were mixed and stirred for 30 seconds to obtain slurry A;
[0082] Add cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to slurry A and continue stirring for 1 min to obtain slurry B;
[0083] Add the micro-active-high-strength microporous composite aggregate into slurry B and continue stirring for 2 minutes to obtain slurry C;
[0084] Steel fiber was added to slurry C and stirred for 1 min to make the slurry evenly mixed to obtain high-fluidity micro-expansion ultra-high performance concrete.
[0085] Example 5
[0086] The difference between this embodiment and embodiment 4 is that the volume content of steel fiber in the high-fluidity micro-expansion ultra-high performance concrete of this embodiment is 3.0%.
[0087] Example 6
[0088] The difference between this embodiment and embodiment 4 is that the volume content of steel fiber in the high-fluidity micro-expansion ultra-high performance concrete of this embodiment is 3.0%, and the micro-active-high-strength microporous composite aggregate is mixed with cement clinker and high-alumina bauxite aggregate in a mass ratio of 3:7.
[0089] Example 7
[0090] The difference between this embodiment and embodiment 4 is that the volume content of steel fiber in the high-fluidity micro-expansion ultra-high performance concrete of this embodiment is 3.0%, and the micro-active-high-strength microporous composite aggregate is mixed with cement clinker and high-alumina bauxite aggregate in a mass ratio of 1:9.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 4 is that the micro-active-high-strength microporous composite aggregate in the large-fluidity micro-expansion ultra-high performance concrete of this embodiment is mixed by cement clinker and high-alumina bauxite aggregate in a mass ratio of 2:8; in terms of mass percentage, the cement clinker is mainly composed of particles with the following particle sizes: 0.15-0.3mm 5%, 0.3-0.6mm: 15%, 0.6-1.18mm 50%, 1.18-2.36mm 30%; in terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm 60%, 1-3mm 40%.
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 1 is that the aggregate in this comparative example is high-alumina bauxite aggregate.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that the ultra-high performance concrete of this comparative example is prepared by the following method:
[0097] According to the above raw material ratio, cement, silica fume, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer were stirred and mixed for 1 minute, water was added, and stirring was continued for about 8 minutes to obtain slurry A;
[0098] Add the micro-active-high-strength microporous composite aggregate into slurry A and continue stirring for 2 minutes to obtain slurry B;
[0099] Steel fiber was added to slurry B and stirred for 1 min to make the slurry evenly mixed to obtain ultra-high performance concrete.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that the ultra-high performance concrete of this comparative example includes the following components, by weight: 700 parts of cement, 120 parts of silica fume, 170 parts of fly ash microspheres, 50 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 220 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the ultra-high performance concrete.
[0102] Comparative Example 4
[0103] The difference between this comparative example and Example 1 is that the ultra-high performance concrete of this comparative example includes the following components, by weight: 700 parts of cement, 120 parts of silica fume, 170 parts of heavy calcium carbonate, 50 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 220 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the ultra-high performance concrete.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that the ultra-high performance concrete of this comparative example includes the following components, by weight: 735 parts of cement, 126 parts of silica fume, 95 parts of fly ash microspheres, 84 parts of heavy calcium carbonate, 1000 parts of micro-active-high-strength microporous composite aggregate, 220 parts of water, 10.5 parts of polycarboxylate water reducer; and steel fiber accounting for 2.5% of the volume of the ultra-high performance concrete.
[0106] Comparative Example 6
[0107] The difference between this comparative example and Example 1 is that in this comparative example, the average diameter of the steel fiber is 0.20 mm, the average length is 14 mm, the average aspect ratio is 70, and the content of the steel fiber is 2.5%.
[0108] Comparative Example 7
[0109] The difference between this comparative example and Example 1 is that in this comparative example, the average diameter of the steel fiber is 0.20 mm, the average length is 14 mm, the average aspect ratio is 70, and the content of the steel fiber is 3.0%.
[0110] Comparative Example 8
[0111] The difference between this comparative example and Example 1 is that the amount of water used in this comparative example is 180 parts.
[0112] After the high-fluidity, slightly-expanding ultra-high performance concrete of Examples 1-8 of the present invention and the ultra-high performance concrete of Comparative Examples 1-8 were mixed, the slump expansion was tested, and the slurry was poured into a standard mold for molding. After standing for 1 day, the mold was removed, and then placed in a standard curing room for standard curing to a specified age, and mechanical properties, durability, and shrinkage properties were tested. The test results are shown in Table 1.
[0113] As shown in Table 1, the high-fluidity micro-expansion ultra-high performance concrete prepared by the method of the present invention has good working performance, mechanical properties, durability, and exhibits micro-expansion effect. The 28d compressive strength of the prepared UHPC can reach more than 250MPa, the flexural strength can reach more than 50MPa, the initial expansion is 720-770mm, the 1h expansion is 680-725mm, the expansion under the 7d autogenous shrinkage test can reach 231με, the expansion under the 180d shrinkage test can reach 113με, and the 28d chloride ion diffusion coefficient can be as low as 3.9×10 -14 m 2 ·s -1 The following. Moreover, relative to comparative example 1, after the present invention co-adds cement clinker and high-alumina bauxite aggregate (Example 1), its compressive strength, flexural strength, durability and working performance are significantly improved, among which the 28d compressive strength improvement rate is 17.1%, and the flexural strength improvement rate is 34.8%. Relative to comparative example 2, the present invention first disperses the silica fume in water and then mixes and stirs it with other raw materials, which greatly shortens the stirring time, and the working performance, mechanical properties and durability are also significantly improved. Relative to comparative examples 3 and 4, the present invention uses co-addition of microspheres and heavy calcium carbonate to significantly improve the working performance of the slurry, avoid aggregate segregation and sedimentation in the slurry, and help to improve the mechanical properties and durability of the slurry. Relative to comparative example 5, the present invention adds an expansion agent, and the resulting UHPC has a good micro-expansion effect, such as Figure 1 and Figure 2 As shown. Compared with Comparative Examples 6 and 7, the present invention utilizes the spatial size effect between the fiber and the aggregate to reduce the fiber length and diameter, which can effectively improve the working performance, mechanical properties, durability and volume stability of the prepared UHPC. Compared with Comparative Example 8, the present invention increases the water-binder ratio, which is beneficial for the expansion agent and anhydrite to produce expansion substances and promote their activity stimulation effect on the system. At the same time, the appropriate increase in the water-binder ratio is beneficial to the reduction of the viscosity of the system, which makes the slurry have good working performance, and then helps to increase the structural density, so that the obtained UHPC has good micro-expansion effect and better mechanical properties.
[0114] Table 1
[0115]
[0116] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-fluidity micro-expansion ultra-high performance concrete, characterized in that: The concrete comprises the following components by weight: 700-800 parts of cement, 120-150 parts of silica fume, 90-110 parts of fly ash microspheres, 80-100 parts of heavy calcium carbonate, 40-60 parts of expansion agent, 1000 parts of micro-active-high-strength microporous composite aggregate, 220-240 parts of water, 10.5-12.5 parts of polycarboxylate water reducer, and steel fiber accounting for 2.5-3.0% of the volume of the high-flow micro-expansion ultra-high performance concrete; the micro-active-high-strength microporous composite aggregate is mixed with cement clinker and high-alumina bauxite aggregate in a mass ratio of (1-3):(7-9); In terms of mass percentage, the cement clinker is mainly composed of particles of the following particle sizes: 0.15-0.3 mm 5-10%, 0.3-0.6 mm 10-20%, 0.6-1.18 mm 40-50%, 1.18-2.36 mm 20-30%; In terms of mass percentage, the high-alumina bauxite aggregate is mainly composed of particles with the following particle sizes: 0-1mm 50-60%, 1-3mm 40-50%; The steel fiber has a diameter of 0.14-0.16 mm, a length of 9-11 mm, and an aspect ratio of 60-70.
2. The high-fluidity micro-expansion ultra-high performance concrete according to claim 1, characterized in that: The expansion agent is mainly composed of a calcium oxide expansion agent and gypsum mixed in a mass ratio of (2-3):
1.
3. The high-flow low-shrinkage ultra-high performance concrete according to claim 1, characterized in that: The cement clinker is silicate cement clinker; the alumina content of the high-alumina bauxite aggregate is not less than 80wt%.
4. The high-flow low-shrinkage ultra-high performance concrete according to claim 1, characterized in that: The cement is ordinary Portland cement or Portland cement with a grade not less than 42.
5.
5. The high-flow low-shrinkage ultra-high performance concrete according to claim 1, characterized in that: The water demand ratio of the silica fume is not more than 125%, and the 28d activity index is not less than 105%; the water demand ratio of the fly ash microspheres is ≤95%, and the 28d compressive activity index is ≥110%.
6. The high-flow low-shrinkage ultra-high performance concrete according to claim 1, characterized in that: The fineness of the heavy calcium carbonate is not less than 325 meshes and not more than 600 meshes.
7. The method for preparing the high-fluidity micro-expansion ultra-high performance concrete according to any one of claims 1 to 6 comprises the following steps: 1) Mix and stir the weighed water and silica fume to obtain slurry A; 2) adding weighed cement, fly ash microspheres, heavy calcium carbonate, expansion agent, and polycarboxylate water reducer to the obtained slurry A, and continuing stirring to obtain slurry B; 3) adding the weighed micro-active-high-strength microporous composite aggregate to the obtained slurry B, and continuing to stir to obtain slurry C; 4) Add the steel fiber to the obtained slurry C and stir evenly to obtain high-fluidity micro-expansion ultra-high performance concrete.
Citation Information
Patent Citations
High-toughness and high-cohesiveness C250 ultrahigh-strength hybrid fiber concrete and preparation method thereof
CN113024189A
Self-curing micro-expansion ultra-high performance concrete and preparation method thereof
CN113480272A
High-modulus ultra-high performance concrete based on artificial high-strength aggregate and preparation method of high-modulus ultra-high performance concrete
CN116003052A
Ultrahigh-performance recycled concrete and preparation method thereof
CN116199475A
Cementitious gypsum-containing binders and compositions and materials made therefrom
CN1257466A